Successful treatment of prostaglandin-induced cystoid macular edema with subtenon triamcinolone - Matsuura K (Dove Medical Press, 2012)
Kazuki Matsuura,1 Shinichi Sasaki,2 Ryu Uotani31Nojima Hospital, Kurayoshi, 2Kushimoto Rehabilitation Center, Kushimoto, 3Tottori University, Yonago, JapanPurpose: Cystoid macular edema (CME) is associated with the use of prostaglandin eye drops after cataract surgery. The study aim was to report on the treatment of two CME patients with subtenon triamcinolone injections.Methods: Case one was a 70-year-old woman who underwent uneventful cataract surgery. Travoprost was administrated at 10 weeks after surgery, and CME occurred at 13 weeks after surgery. Case two was an 85-year-old man who underwent intraocular lens extraction and an intraocular lens suture operation. Latanoprost was readministered after the surgery. The patient complained of blurred vision 3 years later.Results: For both cases, discontinuation of the prostaglandin eye drops, subsequent initiation of treatment with diclofenac eye drops, and subtenon injection of triamcinolone was followed by the rapid disappearance of the CME. After the CME had disappeared for 3 months, the prostaglandin eye drops were resumed. Diclofenac was added in case two. No CME recurrence was seen in either case over 2 years.Conclusion: Subtenon triamcinolone injection can be effective for CME associated with prostaglandin eye liquid after cataract surgery. Prostaglandin eye liquid that causes CME is not necessarily precluded for future use if administered under careful observation.Keywords: cystoid macula edema, subtenon triamcinolone injection, prostaglandin eye drops, cataract surgery